Development of I-SETS Thematic Teaching Materials to Improve Student Character - Siti Munazilah; Agus Yulianto (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
The teaching material focuses on the theme of rain which is discussed through the I-SETS approach (Islamic, scientific, environmental, technological, and social). This study aimed to determine the characteristics, feasibility, and enchancement of student character after using teaching materials. This study uses the Research and Development (R D) method in the form of One Group Pretest-Post-test Design. Data collection techniques through interviews, observation, questionnaires, and test results. Data analysis techniques is quantitative descriptive. The characteristics of the teaching materials that had been developed were viewed from three aspects (content, presentation, and language). This characteristic is supported by validating the feasibility of teaching materials of 86.58% had very feasible criteria. Readability results reached a percentage of 53.20% in the appropriate category for students. The results of the application of teaching materials showed that there is no influence yet of teaching materials on the character development and integrated thinking skills which are based on the N-gain test acquisition of 0.169 from the results of the character questionnaire, 0.218 from the results of the character observastions, 0.085 from pretest-posttest mark. This is due to obstacles when learning online and limited number of encounters.